2021
DOI: 10.1111/1467-9566.13389
|View full text |Cite
|
Sign up to set email alerts
|

A sociology of precision‐in‐practice: The affective and temporal complexities of everyday clinical care

Abstract: The idea of 'precision medicine', which has gained increasing traction since the early 2000s, is now ubiquitous in health and medicine. Though varied in its implementation across fields, precision medicine has raised hopes of revolutionary treatments and has spurred the proliferation of novel therapeutics, the alteration of professional trajectories and various reconfigurations of health/care. Nowhere is the promise of precision medicine more apparent, nor further institutionalised, than in the field of oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 67 publications
(76 reference statements)
0
18
0
2
Order By: Relevance
“…Como resultado do estudo, alguns achados mostraram-se interessantes. Em primeiro lugar, observamos que os especialistas médicos -declaradamente bem preparados e informados sobre os avanços nas áreas da medicina de precisão -abraçam a nova medicina molecular com grande otimismo 30 , antecipando e projetando, para antes de 2049, em combinação ainda com a cirurgia e a radioterapia, uma transformação bem-sucedida no tratamento do câncer por meio do diagnóstico, monitoramento e terapias precisas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Como resultado do estudo, alguns achados mostraram-se interessantes. Em primeiro lugar, observamos que os especialistas médicos -declaradamente bem preparados e informados sobre os avanços nas áreas da medicina de precisão -abraçam a nova medicina molecular com grande otimismo 30 , antecipando e projetando, para antes de 2049, em combinação ainda com a cirurgia e a radioterapia, uma transformação bem-sucedida no tratamento do câncer por meio do diagnóstico, monitoramento e terapias precisas.…”
Section: Discussionunclassified
“…Essa nova forma de tratamento oncológico, ainda em processo de desenvolvimento e maturação de sua aplicação na clínica 24,30,31 , visa determinar a resposta terapêutica ideal por meio da classificação da população e dos tumores em agrupamentos biologicamente apropriados -uma abordagem estratificada que busca substituir os atuais protocolos que são aplicados de forma padronizada em toda a população 23 . Scheuenpflug 32 comenta que a medicina de precisão/personalizada, impulsionada pela evolução da ciência e das tecnologias do século XXI em um contexto de economia global da saúde, procura desenvolver conceitos inovadores e de maior valor terapêutico para pacientes das sociedades industrializadas e envelhecidas.…”
Section: Discussionunclassified
“…Current literature underlines how genomics’ promissory rhetoric is coupled with distinctive affective states, including anticipation, hope and worry, or feelings oriented to the future ( Fortun 2008 ; Adams, Murphy, and Clarke 2009 ). For example, Kenny and colleagues observed that Australian clinicians and patients encountering cancer genomics felt the “problematic pull of survival” regardless of affective or material costs ( Kenny et al . 2021 , 2185).…”
Section: Doing and Feeling Good In Cancer Genomicsmentioning
confidence: 99%
“…10 Standardization and automation of the production of data appear to reduce the possibility for unprecedented events emphasized by Rheinberger. 11 Furthermore, it seems that such research is built on the assumption that there is nothing left to discover with respect to, say, constituents of cells (at least for humans or 5 Kenny et al 2021. For a long-term perspective on the promissory nature of biomedicine, see Löwy, this issue.…”
Section: Experiments: Standardization Automation and Outsourcingmentioning
confidence: 99%